A Ca-based nano bio-coordination polymer providing reversible structural conversion with ability to enhance cytotoxicity of curcumin and induce apoptosis in human gastric cancer AGS cells. Issue 40 (5th October 2022) - Karimi Alavijeh, Roya; Akhbari, Kamran; White, Jonathan M.
Abstract : A new bio-coordination polymer (bio-CP 2 ) was prepared, which indicated a reversible structural conversion in the presence and absence of water. This bio-CP showed positive effects on the water solubility and anticancer performances of curcumin. Abstract : A new nano bio-coordination polymer, bio-CP 2, from an endogenous metal ion (calcium(ii )) and vitamin B3 (nicotinic acid, NA), was synthesized in water by ultrasonic irradiation. The structure of bio-CP 2 reversibly changed under wet conditions. Bio-CP 2, as a thermodynamically stable coordination polymer, was used for the chemical loading of curcumin (CCM) to improve its solubility. The MTT analysis showed improved cytotoxicity of CCM after loading on bio-CP 2 . The flow cytometry analysis of AGS cells (a human gastric adenocarcinoma cell line) after treatment with CCM and bio-CP 2 @CCM indicated cell apoptosis of 3.49% and 78.68%, respectively. These results confirm that bio-CP 2, as a non-toxic coordination polymer, can be used as a drug delivery system to improve the water solubility and anticancer performance of CCM.